Factors affecting specialty choice of postgraduate dental residents in Karachi, Pakistan - Samira Adnan; Maham Muneeb Lone (Journal of the Pakistan Medical Association, 2022)
Objective: To identify factors that influence the choice of specialty of dentistry postgraduate residents in an urban setting. Method: The cross-sectional analytical study was conducted from April to May 2020 at health centres approved for the Fellowship of the College of Physicians and Surgeons training in Karachi, and comprised dental postgraduate residents. Data was collected using a questionnaire distributed using Google Forms. Residents were asked to rate factors that influenced their decision to join their clinical specialty on a 3-point Likert scale. Items were based on the basis of anticipated clinical experiences, specialty-specific factors, personal preferences, and possible constraints. Data was analysed using SPSS 23. Results: Of the 51 subjects, 39(76.5%) were females and 12(23.5%) were males. The overall mean age was 27.7±2.17 years. Besides, 27(52.9%) subjects were from public-sector centres and 24(47.1%) from private-sector centres. Of all the residents, 44(86.3%) chose their specialty because of inclination to treat complex cases, while 43(84.3%) were interested because of the broad range of cases, and 39(76.5%) made their choice because of the reputation of the respective supervisors and institutions. Also, 43(84.3%) residents did not consider the expiry of their fellowship part one exam deadline, or unavailability of a training slot as a specific reason to select a specialty. Compared to males, significantly more females opted for a specialty if it eventually provided career opportunity as faculty (p<0.05). Conclusion: Factors that greatly influenced the residents' choice for postgraduate training specialty were related to anticipated clinical experiences. Continuous...